2022
DOI: 10.3390/cryst12040452
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Au, Ag, and Cu Adatoms on Optical Properties of TiO2 (110) Surface: Predictions from RT-TDDFT Calculations

Abstract: In this paper, real-time time-dependent density-functional theory (RT-TDDFT) calculations are performed to analyze the optical property and charge transitions of a single noble metal atom deposited on rutile TiO2 (110) surface. The model structures are built reflecting the equilibrium positions of deposited adatoms atop the TiO2 surface. The absorption spectra are calculated for all model structures under study. To provide deeper insight into photo-absorption processes, the transition contribution maps are com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…However, a notable distinction for the TiO 2 (001) surface is that the enhancement in absorption is not confined to the x direction; it extends to the y and z directions as well. The observed slight red shift in the calculated absorption spectra aligns with our recent theoretical investigation involving Cu, Ag, and Au adatoms deposited onto the rutile TiO 2 (110) surface [23]. In cases where the noble metal adatom is not strongly bonded to the surface oxygen or other nearest host surface atoms, the calculated electronic structure of the pristine rutile TiO 2 (110) surface closely resembles that of the surface with an attached adatom.…”
Section: Doped Surfacessupporting
confidence: 85%
See 3 more Smart Citations
“…However, a notable distinction for the TiO 2 (001) surface is that the enhancement in absorption is not confined to the x direction; it extends to the y and z directions as well. The observed slight red shift in the calculated absorption spectra aligns with our recent theoretical investigation involving Cu, Ag, and Au adatoms deposited onto the rutile TiO 2 (110) surface [23]. In cases where the noble metal adatom is not strongly bonded to the surface oxygen or other nearest host surface atoms, the calculated electronic structure of the pristine rutile TiO 2 (110) surface closely resembles that of the surface with an attached adatom.…”
Section: Doped Surfacessupporting
confidence: 85%
“…When the Hubbard U parameter for titanium d-orbitals U Ti(d) = 4.2 eV is incorporated, the resulting optical absorption spectrum shows a red shift compared to neglect of the Hubbard correction. Interestingly, despite these adjustments, our analysis reveals that there is no significant difference in the absorption characteristics between the TiO 2 surfaces with and without the Hubbard correction [23,62,63]. This finding suggests that the Hubbard correction does not markedly alter the absorption properties of these surfaces, at least within the range of our study.…”
Section: Pristine Surfacesmentioning
confidence: 48%
See 2 more Smart Citations
“…Summarizing this subsection, we observed that the majority of recent studies on doped TiO 2 have found the accuracy of optical property calculations conducted using several DFT-based computational techniques to be satisfactory. However, a few exceptions exist where more advanced techniques such as TDDFT, GW, or BSE methods were also employed [184,185]. These preferences indicate that despite its acknowledged limitations in describing optical properties, DFT still contributes to exploratory research.…”
Section: Optical Propertiesmentioning
confidence: 99%